The Role of Cognitive Empathy on Adolescents’ Phubbing During Pandemic Covid-19 - Rizkyanti, Charyna Ayu; Edyta, Nabilah; Fitrusti, Nefira Dewi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
During the Covid-19 pandemic, various activities, including the learning process, have shifted to digital platforms. This is a serious concern because teenagers interact more easily with smartphones than pay attention to other people during social interactions, which is called "phubbing". The purpose of this study was to examine the role of cognitive empathy in phubbing among adolescents who use social media. By using the volunteer sampling (opt-in) panel technique, a total of 398 respondents (aged 16-21) were taken part in this study. Respondents filled out two instruments, namely the Phubbing Scale (10 items), the Basic Empathy Scale (9 items). There is an effect of cognitive empathy on phubbing in adolescent social media users, with a contribution value of 38%. The results showed there was a gender difference, with girls reporting higher levels of phubbing and cognitive empathy than boys. This study is the first to provide empirical evidence on the role of cognitive empathy for phubbing on social media among adolescents. This highlights the importance of efforts to indulge our culture as our national identity to stop phubbing becoming the new norm in society, including the younger generation.